2022
DOI: 10.1101/2022.07.16.500312
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PanIN and CAF Transitions in Pancreatic Carcinogenesis Revealed with Spatial Data Integration

Abstract: Spatial transcriptomics (ST) is a powerful approach for cancers molecular and cellular characterization. Pancreatic intraepithelial neoplasia (PanIN) is a pancreatic ductal adenocarcinoma (PDAC) premalignancy diagnosed from formalin-fixed and paraffin-embedded (FFPE) specimens limiting single-cell based investigations. We developed a new FFPE ST analysis protocol for PanINs complemented with novel transfer learning approaches. The first transfer learning approach, to assign cell types to ST spots and integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 86 publications
1
17
0
Order By: Relevance
“…To ensure accurate assessment of PanIN burden, multiple samples were taken from the head, body and tail of each donor organ for histologic analysis. We observed no overt difference in prevalence by anatomic region; PanINs, when present, were typically multi-focal and widely dispersed throughout the gland, consistent with recent reports(36).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…To ensure accurate assessment of PanIN burden, multiple samples were taken from the head, body and tail of each donor organ for histologic analysis. We observed no overt difference in prevalence by anatomic region; PanINs, when present, were typically multi-focal and widely dispersed throughout the gland, consistent with recent reports(36).…”
Section: Discussionsupporting
confidence: 91%
“…As a result, single cell studies of the human pancreas have included very few samples (75,76) or embryonic samples (77) and have focused on endocrine cells less susceptible to degradation. Previous autopsy studies on pancreata of patients deceased with no known pancreas pathology revealed frequent PanINs and KRAS mutations (10,(14)(15)(16)(17)(31)(32)(33)(34)(35)(36)78), but the samples mainly represented older individuals with limited transcriptional profiling performed. In recent years, the advent of single cell technologies has led to in-depth characterization of human pancreatic cancer and its accompanied tumor microenvironment (24,26,60,79,80).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor histology can reveal additional prognostic information, including genomic features. Indeed, recent work used deep learning models to predict genomic alterations and gene expression data from tumor histology [19][20][21] ; other efforts combined genomics and histology to predict prognosis 22 , overall survival 23 , and, leveraging new spatial transcriptomics approaches, molecular heterogeneity of cell states 24 . While genomics and histology offer complementary, synergistic insights into latent tumor biology, clinical deployment of deep-learning-based histology biomarkers requires model transparency demonstrating the histologic features responsible for predictions 25 .…”
Section: Introductionmentioning
confidence: 99%